Binding and Relocalization of Protein Kinase R by Murine Cytomegalovirus - Child, Stephanie J. (American Society for Microbiology (ASM), 2009)
Many viruses have evolved mechanisms to evade the repression of translation mediated by protein kinase R (PKR). In the case of murine cytomegalovirus (MCMV), the protein products of two essential genes, m142 and m143, bind to double-stranded RNA (dsRNA) and block phosphorylation of PKR and eukaryotic initiation factor 2α. A distinctive feature of MCMV is that two proteins are required to block PKR activation whereas other viral dsRNA-binding proteins that prevent PKR activation contain all the necessary functions in a single protein. In order to better understand the mechanism by which MCMV evades the PKR response, we investigated the associations of pm142 and pm143 with each other and with PKR. Both pm142 and pm143 interact with PKR in infected and transfected cells. However, the ∼200-kDa pm142-pm143 complex that forms in these cells does not contain substantial amounts of PKR, suggesting that the interactions between pm142-pm143 and PKR are unstable or transient. The stable, soluble pm142-pm143 complex appears to be a heterotetramer consisting of two molecules of pm142 associated with each other, and each one binds to and stabilizes a monomer of pm143. MCMV infection also causes relocalization of PKR into the nucleus and to an insoluble cytoplasmic compartment. These results suggest a model in which the pm142-pm143 multimer interacts with PKR and causes its sequestration in cellular compartments where it is unable to shut off translation and repress viral replication.